A Study on the Application of One-Phase Controlled Wave Rectifiers for Full Resistive Load in Community - Bambang Gunanto (Politeknik Perkapalan Negeri Surabaya, 2023)
A rectifier is a vital electronic device used to convert alternating current (AC) into direct current (DC), serving critical roles in industrial applications such as Uninterruptible Power Supplies (UPS), constant voltage regulation, motor speed control, and power factor correction. Its versatility extends to supporting small-scale industries, educational institutions, and public utilities, making it a key technology for community energy solutions. This study focuses on the design and implementation of a single-phase controlled rectifier utilizing the Pulse Width Modulation (PWM) method. The PWM approach enables precise regulation of output voltage while improving power factor efficiency. Experimental analysis was conducted under two key conditions to evaluate performance: (1) maintaining a constant resistive load with varying input voltages and (2) adapting to variable resistive loads with a fixed input voltage. These tests measured the rectifier's ability to provide stable output under dynamic operational scenarios. The results indicate that the single-phase controlled rectifier employing PWM demonstrates high reliability and efficiency. It consistently maintains stable output voltages, even when subjected to fluctuations in load or input voltage. These capabilities underscore its potential as a robust energy solution for diverse applications, including renewable energy systems, microgrids, and small-scale industrial processes. By addressing energy challenges and offering dependable performance, the single-phase controlled rectifier with PWM presents an innovative tool for improving energy access in underserved areas. This technology supports sustainability goals and enhances the resilience of energy infrastructure in community-focused projects.